ØªØ£Ø«ÙŠØ± Ø¬Ø§Ø¦ØØ© ÙƒÙˆØ±ÙˆÙ†Ø§ Ø¹Ù„Ù‰ ÙØ§Ø¹Ù„ÙŠØ© Ø¹Ù…Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Sri Sulastri Mayani; Dony Handriawan (Lughatu Ad-dhat, 2022)
This article aims to find the impacts of corona virus outbreak during the process of Arabic teaching and learning (ATL) in MTsN 4 East Lombok. Definitly the reaearch tries to: 1) describe the implementation of ATL during the corona virus pandemic, 2) analyze the problems that are faced by Arabic language teachers in ATL during the pandemic, and 3) display the alternative solutions taken by teachers of MTsN 4 East Lobmok to solve the problems. This qualitative research uses descriptive analysis technique, and several methods in collecting the data such as observations, interviews and documentations. While researchers take a few steps in searching and compiling data systematically, start from data collections, reducting, presenting, conclusions and verifications. The final results of this research show that: 1) the process in implementing ATL during the pandemic in MTsN 4 East Lombok uses two learning system, namely online and offline learning systems. Online learning uses the popular social media application such as Whatsapp to convey their lessons, also uses one-sheet lesson plans and evaluate written worksheet that can be taken and submitted directly to school; 2) there are several problems that are faced by teachers and students during learning process such as students constrained by inadequate facilities, problem in using technology, student focus and enthusiasm in online learning that have a negative effect of student learning outcomes; and 3) the solutions taken by teachers to solve the problems are: a) in learning evaluation, teachers gives an assignment using videos and photos documentations, even though some students get difficult; b) than the teachers will allow them to come to school with health protocols; c) revise the existing lesson plans, while teachers use essentials materials only, d) teachers chose learning in group method to solve the problem related to the technology, e) to motived the students who are disrupted their focus and un-enthusiast to follow online learning, teachers use Q&A method and also story-telling method.